2016
DOI: 10.1186/s12864-016-2372-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis reveals the gene expression profile that specifically responds to IBA during adventitious rooting in mung bean seedlings

Abstract: BackgroundAuxin plays a critical role in inducing adventitious rooting in many plants. Indole-3-butyric acid (IBA) is the most widely employed auxin for adventitious rooting. However, the molecular mechanisms by which auxin regulate the process of adventitious rooting are less well known.ResultsThe RNA-Seq data analysis indicated that IBA treatment greatly increased the amount of clean reads and the amount of expressed unigenes by 24.29 % and 27.42 % and by 4.3 % and 5.04 % at two time points, respectively, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 109 publications
(143 reference statements)
3
34
0
Order By: Relevance
“…Among these, several genes were differentially expressed in the AR formation phase, with higher expression in IBA-treated cuttings than in CK, including ACC oxidase 1 (ACO1). Interestingly, the expression of these genes is induced by exogenous auxin in the rooting-competent cuttings of two distantly related forest species, and there are some similar reports that ACO genes lead to AR formation in mung bean and tomato [ 46 , 47 ]. It appears that IBA-induced ethylene production may contribute to the stimulation of adventitious rooting [ 47 ].…”
Section: Discussionmentioning
confidence: 92%
“…Among these, several genes were differentially expressed in the AR formation phase, with higher expression in IBA-treated cuttings than in CK, including ACC oxidase 1 (ACO1). Interestingly, the expression of these genes is induced by exogenous auxin in the rooting-competent cuttings of two distantly related forest species, and there are some similar reports that ACO genes lead to AR formation in mung bean and tomato [ 46 , 47 ]. It appears that IBA-induced ethylene production may contribute to the stimulation of adventitious rooting [ 47 ].…”
Section: Discussionmentioning
confidence: 92%
“…Chen et al [18] found that an MSB (MS inorganic salt + B5 vitamin) medium supplemented with IBA could directly induce embryogenic calli and that appropriate concentrations of KT could promote the effect of IBA. IBA is used to induce root organogenesis [19], but studies have found that either IBA alone or in combination with KT can directly induce a certain amount of embryogenic callus from the hypocotyl segment. More extensive experiments are yet to be done to determine the mechanism through which IBA acts.…”
Section: Introductionmentioning
confidence: 99%
“…In this experiment, the hypocotyl tissues that were treated with 10 mM H 2 O 2 for 6 h or 24 h, designated as HO6 and HO24, which represent the induction stage and initiation stage of adventitious root development in mung bean seedlings, respectively [ 29 , 30 ], were separately sampled for total RNA extraction, cDNA library construction, and Illumina Solexa RNA paired-end sequencing. The sequencing data and mapping results are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The sequencing data and mapping results are listed in Table 1 . This sequencing generated approximately 93% of the high-quality reads from the samples, and approximately 93% of the quality reads mapped uniquely to the reference sequences that were constructed in our previous study [ 29 , 30 ]. Using the Chrysalis cluster module of TRINITY, we identified a total of 78,697 unigenes from all the samples [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation